Formation of foreign-language communicative competence at the scientific language lessons - Nikitina, Ekaterina (2021)
The article proves that formation of foreign-language communicative competence is one of the core objectives of teaching Russian as a foreign language. The author proves that foreign-language communicative competence is a complex construct which includes linguistic, substantive, and pragmatic competences. Preparatory departments are to create an educational model that would provide formation of foreign-language communicative competence.